Experimental investigation on SS202 using tubular and double D tubular electrode tool in electrical discharge drilling machining - Pandiyan, Manikandaprabu (Strojniški vestnik, 2024)
To meet the demands of the manufacturing industry, a more robust approach is needed for current manufacturing processes. Machining of very hard materials with excellent dimensional accuracy and surface integrity is a challenging task, Currently, the electrical discharge machining (EDM) process is the optimal solution for machining such materials. Electrical discharge drilling machines find applications in various sectors such as aerospace, automobile and medicine. In this research, two different brass electrode geometries are considered: tubular electrode tool (TET) and double D tubular electrode tool (DDTET) on an SS202 work-piece. The input parameters of peak current (PI), pulse time ON (PONT), and pulse time OFF (POFFT) were varied. The output response measured and compared were material removal rate (MRR) and over cut (OC). The Taguchi technique was used to design the l16 orthogonal array (OA) experiment, and analysis of variance (ANOVA) was employed for result analysis using Minitab20 statistical software package. The results showed that the DDTET method produced significantly better MRR and OC improvements of 21.66 % and 2.28 % respectively. Additionally, a study was conducted on the formation of the recast layer (RL) and the heat affected zone (HAZ).
Keywords: analysis of variance; ANOVA; heat affected zone; material removal rate; modificirana geometrija elektrod; modified electrode geometry; nadmera; over cut; pretaljeni sloj; recast layer; stopnja odvzema materiala